2019
DOI: 10.1371/journal.pbio.3000182
|View full text |Cite
|
Sign up to set email alerts
|

Evolthon: A community endeavor to evolve lab evolution

Abstract: In experimental evolution, scientists evolve organisms in the lab, typically by challenging them to new environmental conditions. How best to evolve a desired trait? Should the challenge be applied abruptly, gradually, periodically, sporadically? Should one apply chemical mutagenesis, and do strains with high innate mutation rate evolve faster? What are ideal population sizes of evolving populations? There are endless strategies, beyond those that can be exposed by individual labs. We therefore arranged a comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…In yeast, duplicated genes have also been shown to be transcriptionally diverged, particularly in WGD (19). In a wider study looking at transcriptional changes of duplicated genes under different stress conditions, it was observed that one of the gene copies was more transcriptionally plastic than the other (23). These all indicate that transcriptional divergence plays an important role in maintaining duplicated genes in the genome and expanding the phenotypic plasticity of the organism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In yeast, duplicated genes have also been shown to be transcriptionally diverged, particularly in WGD (19). In a wider study looking at transcriptional changes of duplicated genes under different stress conditions, it was observed that one of the gene copies was more transcriptionally plastic than the other (23). These all indicate that transcriptional divergence plays an important role in maintaining duplicated genes in the genome and expanding the phenotypic plasticity of the organism.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evolution, in particular with Escherichia coli and S. cerevisiae, has been of unprecedented relevance to unveil evolutionary pathways underlying the origin of adaptations, including as examples the adaptation of E. coli to citrate in the known Lenski evolution experiment (13)(14)(15)(16)(17) and heat stress, nutrient limitations, antibiotic treatment, or tolerance to glycerol in S. cerevisiae (18)(19)(20)(21)(22)(23)(24). Its use to understand the adaptation to ethanol has been addressed in only a few studies, while using ethanol as additional carbon source (4,5,25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One limitation of current studies within the field is that they can be difficult to compare due to variations in experimental parameters, such as species, antibiotics, or other experimental conditions ( 17 ). Given the unique evolutionary pathways at different antibiotic concentrations, systematic mapping of these evolutionary landscapes could provide an improved understanding of which conditions pose the highest risk by allowing direct comparisons between different antibiotic concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…By simulating a simplified 2-species community, we could compare the efficacy of different selection regimens with relative ease, unlike experimental comparisons that would require concerted efforts from multiple labs [24]. Additionally, by analyzing evolving communitiestheir functions and member species phenotypes-we could begin to understand evolutionary dynamics during community selection.…”
Section: Introductionmentioning
confidence: 99%